Exploring the challenges of quitrent rights on land use, development and ownership in the Eastern Cape - Malgas, Phucuka Penelope (Department of Construction Economics and Management, 2025)
This research examines the restrictions of the quitrent rights system and the impact thereof on land and economic development in the Eastern Cape province of South Africa. To appreciate the current challenges, one has to understand the historical development and complexities of the quitrent rights system. Many quitrent titles were surveyed in the former Transkeian and Ciskeian Territories between 1890 and 1923. Formal title deeds were registered in the Deeds Registry in respect of the affected land parcels in various categories that were either residential, arable or commonage portions. The quitrent right holders were later moved from the land into betterment schemes, and “permissions to occupy” (PTO) were allocated to them. In the process, the state ignored the existing quitrent rights and began to construct schools, hospitals, dams, nature reserves and roads over the land which had been accorded a quitrent. Even though some quitrents lapsed due to forfeiture or cancellation, most of these quitrent titles in the former Transkeian Territories are still reflected in the Deeds Registry. Until an investigation reveals that a (still registered) quitrent has lapsed, it must be regarded as valid and enforceable. In terms of the Deeds Registries Act 47 of 1937, an immovable property can only be registered against an approved Surveyor-General Diagram, as per the Land Survey Act 8 of 1997. An immovable property affected by a quitrent is not eligible for registration at the deeds office as the approved diagram of such a property is encumbered by a caveat preventing registration. Registration will only be permissible upon providing proof that compensation was paid to the quitrent holder or beneficiary. The impact on land administration is such that properties affected by the quitrent right system cannot be registered at the Deeds Office and thus cannot be disposed of nor transferred. This means no notarial lease agreements can be registered on any land affected by a quitrent for development purposes. This poses a negative impact on investment and economic development. The study investigates the challenges and implications that the quitrent rights have on land use, development and ownership. It identifies and presents possible workable solutions in resolving the challenges presented by the existence of quitrents. Finally, it determines the role that government can play in resolving the land ownership dilemma that the quitrents present